CD20+CD22+ADAM28+ B Cells in Tertiary Lymphoid Structures Promote Immunotherapy Response - Wu, Zhenghao; Zhou, Junjie; Xiao, Yunxiao; Ming, Jie; Zhou, Jing; Dong, Fang; Zhou, Xiaoqi; Xu, Zhuoshuo; Zhao, Xiangwang; Lei, Ping; Huang, Tao (Frontiers in Immunology, 2022)
Background: As the indication for immunotherapy is rapidly expanding, it is crucial to accurately identify patients who are likely to respond. Infiltration of B cells into many tumor types correlates with a good response to immune checkpoint inhibitors (ICI) therapy. However, B cells' roles in the anti-tumor response are far from clear. Methods: Based on single-cell transcriptomic data for ICI-treated patients, we identified a B cell cluster (BIR, ICI-Responsive B cells) and described the phenotype, cell-cell communication, biological processes, and gene signature, and prognosis value of BIR cells through bioinformatic analysis, tissue immunofluorescence and animal experiments. Surgery samples from 12 NSCLC patients with adjuvant checkpoint blockade were evaluated as external validation. Results: BIR cells were identified as a subset of CD20+CD22+ADAM28+ B cells with a memory phenotype. Bioinformatic analysis revealed BIR cells had enhanced cell viability and epigenetic regulation, and that ALOX5AP, MIF, and PTPRC/CD45 expressed by myeloid cells may be critical coordinators of diverse biological processes of BIR cells. Immunofluorescence confirmed the presence of BIR cells in tertiary lymphoid structures (TLSs) in skin SCC, RCC, CRC, and breast cancer. BIR-associated gene signatures correlate with positive outcomes in patients with melanoma, glioblastoma, NSCLC, HNSCC, or RCC treated with ICI therapy, and BIR cells density predicted NSCLC patients’ response to checkpoint immunotherapy. In line with this, melanoma-bearing mice depleted of BIR cells were resistant to ICIs. Conclusions: CD20+CD22+ADAM28+ BIR cells were present in cancer-associated TLS and promoted the response to ICI therapy